2018
DOI: 10.1126/sciimmunol.aar3451
|View full text |Cite
|
Sign up to set email alerts
|

Tumor immune evasion arises through loss of TNF sensitivity

Abstract: Immunotherapy has revolutionized outcomes for cancer patients, but the mechanisms of resistance remain poorly defined. We used a series of whole-genome clustered regularly interspaced short palindromic repeat (CRISPR)-based screens performed in vitro and in vivo to identify mechanisms of tumor immune evasion from cytotoxic lymphocytes [CD8 T cells and natural killer (NK) cells]. Deletion of key genes within the tumor necrosis factor (TNF) signaling, interferon-γ (IFN-γ) signaling, and antigen presentation path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
226
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 285 publications
(268 citation statements)
references
References 45 publications
17
226
1
Order By: Relevance
“…An alternative option to amplifying the immune response, is to reduce the threshold of a tumor cell to respond to immunotherapy. Using a CRISPR/Cas9 screen, Kearney et al 2018, showed that the suppression of TNF, Interferon (IFNγ) and antigen presentation were key mechanisms by which tumors can evade the attack of CLs [151]. This matched well with previous clinical data showing that IFNγ plays an important role in the efficacy of ICIs [152], but for the first time suggested TNF signaling was also an important component.…”
Section: Combination With Immunotherapysupporting
confidence: 70%
“…An alternative option to amplifying the immune response, is to reduce the threshold of a tumor cell to respond to immunotherapy. Using a CRISPR/Cas9 screen, Kearney et al 2018, showed that the suppression of TNF, Interferon (IFNγ) and antigen presentation were key mechanisms by which tumors can evade the attack of CLs [151]. This matched well with previous clinical data showing that IFNγ plays an important role in the efficacy of ICIs [152], but for the first time suggested TNF signaling was also an important component.…”
Section: Combination With Immunotherapysupporting
confidence: 70%
“…With regard to understanding the role of TNF to both immune‐mediated anticancer activity and irAEs, preclinical data are conflicting. For example, a significant preclinical role for TNF in the killing of tumor cells by both CD8 + cytotoxic T lymphocytes and natural killer cells has been uncovered recently . In contrast, Liu et al.…”
Section: Discussionmentioning
confidence: 99%
“…(2) Instead of using the genome-scale functional screens in cancer cell lines (DepMap 12,13 ) in the first step of ISLE or INCISOR, we analyze genome-wide CRISPR screens performed in co-cultures of cancer and T-cells, identifying genes whose knock-out enhances or prevents T-cell mediated killing. To this end we incorporated four such genome-wide CRISPR screens publicly available [51][52][53][54] . Since two of them involve treatment of anti-PD1/PDL1, we used these two as the basis for identifying GIs involved in anti-PD1 response prediction 52,54 ; whereas the remaining two screens, identifying those genes involved in generic immune response 51,53 , were used to infer GIs for anti-CTLA4 response prediction.…”
Section: Identifying Genetic Interaction Networkmentioning
confidence: 99%
“…To this end we incorporated four such genome-wide CRISPR screens publicly available [51][52][53][54] . Since two of them involve treatment of anti-PD1/PDL1, we used these two as the basis for identifying GIs involved in anti-PD1 response prediction 52,54 ; whereas the remaining two screens, identifying those genes involved in generic immune response 51,53 , were used to infer GIs for anti-CTLA4 response prediction. (3) We focused on the mediators of resistance to immune checkpoint therapies using synthetic rescue (SR) interactions, as no statistically significant SL interaction partners were identified via ISLE for either PD1 or CTLA4.…”
Section: Identifying Genetic Interaction Networkmentioning
confidence: 99%